Toxicity assessment and degradation of benzoquinone by ZnO photocatalytic oxidation process - Akyol, Abdurrahman (Desalination Publ, 2019)
This study aims in the photocatalytic degradation of a synthetic aqueous solution of 1,4-benzoquinone (BQ) in a batch slurry reactor in the presence of photocatalyst using ultraviolet light at 365 nm. The removal of intermediate products resulting from the degradation of BQ is also investigated by total organic carbon (TOC) analysis. The effects of various process variables such as initial pH (5-10), initial BQ concentration (50-500 mg/L), light intensity (12-36 W), catalyst type and loading (ZnO and Ti02, 0.5-2.5 g/L), and reaction time (0-90 min) on the removal efficiency have been examined. The results show that the BQ and TOC removal efficiencies are both affected by the solution pH, and the maximum removal efficiencies are observed at pH 6 for BQ and pH 7 for TOC in the pH range of 5-10. Removal efficiencies are inversely related to the initial BQ concentration and directly related with light intensity. ZnO exhibits higher photocatalytic activity than Ti02, and removal efficiencies increase with higher catalyst loading. As a result, maximum BQ and TOC removal efficiencies are obtained as 98% and 78%, respectively, at the experimental conditions (Co = 50 mg/L BQ and 32.7 mg/L TOC, pH 6-7, 2.5 g/L ZnO, >12 W, 90 min). In addition, a toxicity test was also carried out to evaluate the toxicity of the untreated and treated BQ solutions. Toxicity was measured with the luminescent bacteria Vibrio fisheri test. The results showed a decrease in toxicity as BQ degraded, and toxicity reduced to the 49% level of inhibition at the end of 90 min. This study demonstrated that the photocatalytic oxidation process has a satisfactory potential for the wastewater with a high organic content and toxicity purification.
Keywords: Toxicity; Advanced treatment technologies; Photocatalytic degradation; p-Benzoquinone; Zinc oxide; Titanium dioxide